Prognostic significance of combined PD-L1 expression in malignant and infiltrating cells in hepatocellular carcinoma treated with atezolizumab and bevacizumab - Lee, Jaejun; Yoo, Jae-Sung; Kim, Ji Hoon; Lee, Dong Yeup; Yang, Keungmo; Kim, Bohyun; Choi, Joon-Il; Jang, Jeong Won; Choi, Jong Young; Yoon, Seung Kew; Han, Ji Won; Sung, Pil Soo (Frontiers in Immunology, 2024)
BackgroundProgrammed death-ligand 1 (PD-L1) expression is abundant not only in malignant cells but also in infiltrating cells within the tumor microenvironment (TME) of hepatocellular carcinoma (HCC). This study explored the association between PD-L1 expression in TME and outcomes in HCC patients treated with atezolizumab plus bevacizumab (AB), emphasizing the implications of PD-L1 expression in both malignant and tumor-infiltrating cells.MethodsThis study included 72 patients with HCC who underwent percutaneous core needle liver biopsy before AB treatment between September 2020 and December 2023. PD-L1 expression on tumor tissues was assessed using the combined positive score (CPS) with cutoff values of 1 and 10, utilizing antibody clone 22C3 (Dako).ResultsThe distribution of PD-L1 CPS included 24 patients with CPS <1, 33 patients with CPS 1–10, and 15 patients with CPS ≥10. Significant differences in overall survival (OS) were observed across the three groups, with CPS ≥10 showing the highest survival rates (p = 0.010). Patients with CPS ≥10 had better OS than those with CPS <10 (median OS 14.8 vs. 8.3 months, P = 0.046), and CPS ≥1 had better OS than CPS <1 (P = 0.021). For progression-free survival (mPFS), the CPS ≥10 group had the highest median PFS of 11.0 months among the three groups (P = 0.044). Objective response rates (ORR) were higher in the PD-L1 CPS ≥10 group than in the 1-10 and <1 group (53.3%, 27.3%, and 16.7%, respectively; P = .047). Multivariate analysis identified that PD-L1 expression ≥10 and ≥1 were associated with favorable outcomes regarding OS (hazard ratio [HR] 0.283, P = .027 and HR 0.303, P = .006, respectively).ConclusionsCombined analysis of PD-L1 expression in malignant and tumor-infiltrating cells can be a promising biomarker for the prognosis of HCC patients treated with AB.